Chars and Activated Carbons Prepared from Asturian Apple Pulp - E. Fernandez; T.A. Centeno; F. Stoeckli (Adsorption Science & Technology)
Asturian apple pulp was carbonised under nitrogen at 400°C and 750°C and subsequently activated with CO 2 at 750°C. The resulting active carbon exhibited properties in line with those expected from precursors of vegetable origin, with the carbonisation stage appearing to have only a limited influence on the final porosity. In the case of carbonisation at 400°C, the initial micropore system of the char was accessible to dichloromethane, CO 2 and water, but presented a strong gate effect at ca. 0.35–0.40 nm. The pore volume, W 0 , was equal to 0.13 cm 3 /g and the average pore width 0.70 nm. The pore size distribution was obtained from CO 2 adsorption at 0°C, using isotherms derived from computer modelling. With the char prepared at 750°C, the initial porosity was only accessible to water and its presence was confirmed by extrapolation of W 0 for the activated carbons.